Effectiveness of functional training on cardiorespiratory parameters: a systematic review and meta-analysis of randomized controlled trials - Rezende Barbosa, Marianne Penachini da Costa de; Oliveira, Vinicius Cunha; Silva, Anne Kastelianne França da [UNESP]; Pérez-Riera, Andrés Ricardo; Vanderlei, Luiz Carlos [UNESP] (Wiley, 2018)
Background: Functional training is a new training vision that was prepared from the gesture imitation of daily activities. Although your use has become popular in clinical practice, the influence of the several cardiorespiratory adjustments performed during the functional training in different populations and conditions is unknown. So, the aim of this systematic review was to gather information in the literature regarding the influence of functional training on cardiorespiratory parameters. Methods: We conducted search strategies on MEDLINE, PEDro, EMBASE, SportDiscus and Cochrane to identify randomized controlled trials investigating the effects of functional training on cardiorespiratory parameters. Methodological quality of the included studies was assessed using the PEDro scale. Grading of Recommendations Assessment, Development and Evaluation (GRADE) summarized the evidence. Results: Five original studies were included. Effects favoured functional training on oxygen consumption (VO2) at intermediate-term follow-up: weighted mean difference −1·0 (95% CI: 5·4–3·3), P = 0·642, and a small and not clinically important effect observed on VO2 favouring control at intermediate-term follow-up (i.e. mean difference of 1·30 (95% CI 1·07–1·53), P<0·001). Conclusion: According to the GRADE system, there is very low quality evidence that functional training is better than other interventions to improve cardiovascular parameters. This result encourages new searches about the theme.
Keywords: blood pressure; exercise therapy; heart rate; meta-analysis; oximetry; oxygen consumption; respiratory rate